Cepharanthine may inhibit the proliferation of prostate cells by blocking the EGFR/PI3K/AKT signaling pathway: comprehensive network analysis, molecular docking, and experimental evaluation - Huang, Yin; Bai, Jingxing; Ran, Biao; Li, Jinze; Chen, Bo; Chen, Zeyu; Chen, Jie; Wang, Yan; Li, Jin; Dong, Qiang; Wei, Qiang; Cao, Dehong; et al. (Frontiers in Pharmacology, 2025)
IntroductionPharmacological studies have confirmed that Cepharanthine (CEP) can exert anti-inflammatory, antioxidant and anti-fibrotic effects. However, there is no systematic study on whether CEP targets and regulates the core pathological link of benign prostatic hyperplasia (BPH) - matrix hyperplasia.MethodsFirst, the CEP structure was obtained through PubChem. Combined with BPH targets from the GeneCards/OMIM/TTD database, potential targets were obtained by intersection using Venny 2.1. Then, the PPI network was constructed using STRING, and top 20 core targets were identified using Cytoscape 3.9.1. GO/KEGG enrichment analysis was performed using the DAVID database. Based on the CB-Dock platform, CEP was molecularly docked with key targets, the protein structure was derived from AlphaFold2 and PDB, and the binding energy was calculated by the VINA algorithm. Furthermore, human prostate stromal cells WPMY-1 and benign prostatic hyperplasia cells BPH-1 were used as a model. The Celigo full-field scanning system dynamically monitored proliferation from 0 to 96 h, DNA synthesis was quantified by EdU staining, and apoptosis was detected by Annexin V-APC/PI or Annexin V-FITC/PI double staining flow cytometry. Finally, the effect of CEP on the expression of key target genes was analyzed by Western blot.ResultsNetwork analysis showed that 96 cross-targets were significantly enriched in the PI3K-AKT, MAPK and HIF-1 pathways. Molecular docking confirmed that CEP strongly bound to EGFR (−9.2 kcal/mol), AKT1 (−7.7 kcal/mol), and FN1 (−9.6 kcal/mol). In vitro experiments showed that CEP inhibited WPMY-1 (IC50 = 6.396 μM) and BPH-1 (IC50 = 2.355 μM) proliferation in a dose-dependent manner. Treatment of BPH-1 and WPMY-1 cells with 2.5 μM and 5 μM CEP for 48 h, respectively, significantly reduced the proportion of EdU+ cells in both cell lines. Celigo counting revealed a significant decrease in both cell lines after 24–96 h of CEP treatment. Flow cytometry revealed a significant increase in the total apoptotic rate of both WPMY-1 and BPH-1 cells after CEP treatment. Western blot analysis revealed that CEP inhibited EGFR and AKT phosphorylation and FN1 expression in WPMY-1 and BPH-1 cells in a dose-dependent manner.ConclusionThis study confirmed for the first time the effectiveness of CEP in targeted regulation of prostatic hyperplasia. However, the in vivo efficacy needs to be verified in testosterone-induced animal models in the future.